PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN PADA SISWA SMA - Fahrozi, Wirhan; Gunawan Hts, Dedek Indra (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Learning media is one means of channeling messages and learning information. Well designed learning media, is very helpful for students in digesting and understanding the subject matter. The development of information technology in globalization and information today, spurred the development of learning media increasingly advanced a well. Based on the research conducted it can be said that the teacher's paradigm when utilizing information and communication technology in learning is still limited to the use of ICT-based computer media as a presentation material in the learning process. The use of technology as a learning medium in the teaching and learning process can facilitate teaching methods in communicating and interacting with students both in the classroom and outside the classroom. The need for technology in the realm of education is not new the use of technology to form conducive and innovative learners. This utilization proved to play a major role in the smooth process of learning